BETWEEN BEING LANDLESS AND WATTERLESS: TERRITORIAL CONFLICTS AND RESISTANCE OF THE SUBJECTS CAMPED IN THE IRRIGATED PERIMETERS OF PETROLINA-PE - Irineu de Franca, Diego Pessoa [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2023)
mechanisms for the private use of irrigable areas, intensify the conflicts that express the antagonisms between the subjects that defend the right to the territory and their ways of life and those who seek only economics profits, of those who fight for the land-water as means of social reproduction and of those who hold these means as capitalist monopoly, which imposes the generalized precariousness of work. This study was built from fieldwork that, in addition to the oral reports, allowed an ethnographic experience of the conflicting geography in the Dom Tomas Balduino, Sitio Riacho and Democracia camps, both located in the interior of perimeter Pontal-Petrolina-PE. Such qualitative data are interpreted in the light of a critical theory that challenges us to inventiveness by stimulating thoughts about daily life in its singular, particular and universal aspects.This text aims to analyze the territorial conflicts and resistance in the areas of the irrigated perimeters, in the region of Petrolina-PE. In this region, the expansion of a model of globalized fruit production, endowed with vast technical and financial resources, has reconfigured the territory and intensified the private appropriation of land, water and nature by large companies. Capital and the State, when create
Keywords: Conflicts; territories; resistances; perimeters; irrigated